School performance is age appropriate with support services in very preterm children at 11 years of age - Anna Nyman; Tapio Korhonen; Liisa Lehtonen; Leena Haataja; PIPARI Study Group (Blackwell Publishing Ltd, 2022)
Aim: This Finnish regional birth‐cohort study compared the school performance of very preterm and full‐term children when they reached 11 years of age.
Methods: Teachers rated the educational abilities of 123 preterm children and 133 full‐term controls at the age of 11 years as well as the support services they received. The children were all born in the Turku University Hospital between 2001 and 2005. In the preterm group, neurosensory impairments were confirmed at two years of corrected age, and full‐scale intelligence quotient (IQ) was assessed at 11 years of age using the Wechsler Intelligence Scale, Fourth Edition.
Results: Educational abilities, including academic skills and classroom functioning, did not differ between the two groups after excluding the children with a full‐scale IQ < 70. However, 40% of the preterm group and 26% of the controls had received at least one support service (p <0.02). The 13 preterm children with a full‐scale IQ <70 and the 10 with neurosensory impairment received more support services. Boys in both groups displayed more classroom‐functioning problems than girls.
Conclusion: A full‐scale IQ ≥ 70 and age‐appropriate educational abilities do not exclude a significant need for support services in very preterm children at the age of 11 years.